SYNTHESIS OF TITANIUM DIOXIDE (Ti02) NANOCRYSTALLINE FROM TITANIUM TETRACHLORIDE (TiCLO AND ITS APPLICATION IN DYE SENSITIZED SOLAR CELLS (DSC) - AHMAD, ITA ATHIRAH (2012)
Titanium dioxide (Ti02) has been extensively studied as it can be applied to many different applications. Ti02 nanocrystalline has several unique properties that enable them to be desired for many applications and make the production of Ti02 nanomaterial very important and in demand. Multitude of methods and processes are available to synthesize these Ti02 nanomaterials. The ability to manipulate and control the method is the key in producing these nanomaterials with specific properties for the desired applications. Sol-gel hydrothermal method is a very flexible and cost-effective method that has been employed to produce Ti02 nanocrystalline. This thesis presents the experimental study on the method to produce titanium dioxide (Ti02) nanocrystalline by using sol-gel hydrothermal method to be used as photoelectrode materials for dye solar cells (DSC). A simple sol-gel hydrothermal technique which can be easily controlled and reproduced is used to obtain nanocrystalline titanium dioxide (Ti02). By hydrolyzing titanium tetrachloride, TiC^ in a mixture of hydrochloric acid (HC1) and deionized water, Ti02 nanopowder was obtained after calcinations at 400°C. The effect of two parameters which are pH value and the presence of surfactant were studied on the morphology and microstructure ofthe synthesized Ti02 nanocrystalline. The samples have been characterized using FESEM, TEM, XRD and BET and their structure-properties relationships were compared based on I-V characteristic and UV-vis optical absorption. Photoelectrode materials based on Ti02 were developed and their influences on the performance of fabricating DSCs were tested under simulated AMI .5 sunlight illumination with 100 mW/cm light output. Films developed from smaller particles have an advantage in providing a larger surface area and have a greater number of contact points, allowing for greater dye adsorption. Based on the study to optimize the synthesized parameter of Ti02 nanoparticle, the optimum pH value during hydrolysis process has to be at pH 2 while the better surfactant to be used is tetramethylammonium hydroxide (TMAOH). In conclusion, it is important to optimize the surface area by manipulating the parameter that can enhance the morphology of the samples in order to surpass the performance ofthe integrated DSCs.